Analisis Faktor Potensi Penyebab Kecelakaan Lalu Lintas Kendaraan Bermotor - Endang Sugiharti; Muhammad Saleh; Mustikasari Mustikasari (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The purpose of this research is to determine and analyze the level of accidents and the main factors that have been the source of motorized-vehicle traffic accidents in the city of Namrole. The research method used was semi-quantitative analysis, that was the failure mode effect analysis method to analyze the data obtained. This type of research is a descriptive study consisting of: Field Studies and Literature Studies. Research results from the results of brainstorming can be seen that there are several types of causes of traffic accidents, the factors are man, machine, systems, and surroundings.